Characterization of breast cancer tumors in older patients who show de novo resistance to endocrine therapy - Yumiko Ishizuka; Yoshiya Horimoto; Men Yuan; Yuko Ueki; Hiroko Onagi; Harumi Saeki; Takuo Hayashi; Tsuyoshi Saito; Takahiko Kawate; Takashi Ishikawa; Hidetaka Eguchi; Junichiro Watanabe; et al. (Scientific Reports)
Abstract The standard treatment for hormone receptor-positive breast cancer in good general condition is curative surgery followed by endocrine therapy. However, for older patients, endocrine therapy alone is sometimes chosen instead of curative surgery due to health conditions or personal preference, though this is not yet a standard approach. It is crucial to develop elderly-specific treatment strategies, potentially establishing endocrine therapy alone as a standard option. While endocrine therapy is generally effective, some patients show disease progression from the beginning due to de novo resistance. Hence, identifying such tumors is essential to determine who may benefit from endocrine therapy alone. Fifty-one patients aged over 70 years with estrogen receptor-positive and human epidermal growth factor receptor 2-negative invasive breast cancer who were treated with endocrine therapy instead of curative surgery were retrospectively investigated. Genes possibly related to de novo resistance to endocrine therapy were analyzed using a gene expression panel. Of the 51 patients, three patients showed progressive disease (PD) within 6 months of starting endocrine therapy. Gene expression analysis revealed that some genes, including those related to the cell cycle, such as CDKN3, were expressed at higher levels in the PD group compared with the non-PD group. Among these, CDKN3 retained significantly high expression in the PD group, even after analyzing more samples (log2 fold change, 1.99; P = 0.005). Public mRNA microarray data analysis revealed that patients with high CDKN3 tumors had worse outcomes. We identified several genes possibly involved in the de novo resistance to endocrine therapy. Our data indicate CDKN3 to be a predictive marker for de novo endocrine therapy resistance in older patients with breast cancer. We hope that our data will contribute to further research to establish tailored treatments for elderly breast cancer patients.